A mid to late Holocene environmental history of Munsa archaeological site, Uganda - Bunny, Julius Lejju (Trinity College (Dublin, Ireland). Department of Geography, 2005)
Multi-proxy palaeoenvironmental data in the form of microfossil pollen, fungal spores, phytoliths and charcoal have provided a means of reconstructing the mid to late Holocene environmental history of the Munsa archaeological site, Uganda. The palaeoenvironmental data are discussed within a chronological framework provided by fifteen AMS 14C dates; eleven of the dates are for plant macrofossils, while the other four are for bulk sediment samples.. The data were extracted from sedim ent cores obtained from Munsa II, which is today a papyrus-dominated swamp, located within an area described by earthworks that form part of the archaeological site at Munsa.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin